PRIVATIZATION AND THE POLITICS OF SOLID WASTE MANAGEMENT IN GHANA: LESSONS FROM EXPERIENCES - Owusu-Sekyere, E.; Toku, A.; Mabe, F. N. (UDS International Journal of Development, 2023)
Advocates claim that market-assisted policies involving public-private partnerships (PPP) promote economic development and improve efficiency. Counter arguments are that such partnerships often favor the private sector while the underprivileged and service beneficiaries are forced to make difficult compromises. PPP is a triple helix enterprise with the State as a supervisor, the private sector as service provider, and households as consumers. This paper examined households’ satisfaction with PPP in solid waste management in Kumasi, Ghana, after 25 years of implementation. Using multiple methodological approaches and draped in the SERVQUAL model, gaps between performance and customer expectation were revealed. The gaps were observed to be due to limited household understanding of the contractual relationship between the private sector and other industry players, a relationship that is often cloaked in secrecy under the pretext of business confidentiality which conceals the public gaze. It is argued that community participation foregrounds the everyday processes that help such policies to get traction in particular locations. Building on this, the paper outlines very important issues for the State in pursuing PPP as an approach for managing solid waste. Keywords: Customer Satisfaction, Ghana, Privatization, Waste Management, SERVQUAL